Proyecto fotográfico en torno a las emociones, sensaciones e historia de un caso de abuso sexual - Ochoa Díaz, Lenny Angela (2024)
The present work consists of a photographic project that focuses on visually capturing the effects, sensations and emotions linked to a real story of child sexual abuse. It consists of 61 photographs and a documentary video essay, which are presented through a web portal. In the creation of this project, various visual treatments, photographic genres and formats have been used. The elements that are part of the exhibition are intended to be a means of visual expression that communicates and encapsulates the complexity behind this situation with respect to the identity of the victim, the profile of the aggressor and the lasting effects of this experience. In this way, it seeks to be a contribution to the dialogue around sexual abuse, offering a testimonial perspective that had previously remained hidden. It is essential to highlight the importance of approaching this sensitive topic with sensitivity and respect. The project seeks to open a space for reflection and awareness around child sexual abuse, highlighting the voice of those whose experiences have often been silenced.